An Analysis of Speech Acts Used By The English Teacher In An Informal Context at SMK Kesehatan Hamzar Maraqitta’limat Pringgabaya - Mardiyanti, Sri; Fikri, Zaenul (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The study aims to analyse the types of speech acts used by English Teacher in informal context at SMK Kesehatan Hamzar Maraqitta’limat Pringgabaya. Speech acts are an important aspect in the interaction between teachers and students, especially in creating a comfortable and effective learning environment. A qualitative descriptive approach was used im this study, with observation and recording methods as the main instruments of data collection. The data were analysed based on the theory of speech acts which include locution, illocution, and perlocution, used by English Teacher. The results showed that teacher were more likely to used illocutionary speech acts such as directive acts to instruct, invite, warn, and suggest. The use of  informal speech acts is effective in increasing friendly interaction between Teacher and students. This study aims to determine the types of speech acts used by English Teacher in informal context at SMK Kesehatan Hamzar Maraqitta’limat Pringgabaya.